Effect of reductive soil disinfestation on melon fusarium wilt and soil metabolomics - Xuelian Ren; Xiaodi Liu; Zhaoran Zhang; Jialin Shao; Zenggui Gao; Yufei Huang (Scientific Reports)
Abstract Reductive soil disinfestation (RSD) represents an environmentally eco-friendly approach for controlling Fusarium wilt, a prevalent soil-borne disease. This method not only has the potential to suppress disease occurrence but also to enhance the activity of soil microorganisms and nutrients levels. Soil metabolites play a critical role in shaping microbial community composition and regulating pathogen abundance. We designed a potted RSD treatments system to grow melons and applied it to the greenhouse. By evaluating its impacts on melon Fusarium wilt disease occurrence and soil metabolites composition using survey statistics and soil metabolomics sequencing analysis. Our findings revealed that RSD treatments using rice and corn straws significantly markedly diminished the Fusarium wilt disease index. Specifically, pot experiments demonstrated that treatments with rice and corn straw notably increased melon plant height and above-ground biomass. Moreover, through non-targeted metabolomics analysis, we further explored alterations in soil metabolites following treatment with rice and corn straw. The results demonstrated that RSD significantly altered soil metabolites. Differential metabolites were notably enriched in pyrimidine metabolism and ABC transporter pathways. Overall, our results indicate that RSD holds promise in preventing melon Fusarium wilt occurrence while potentially enhancing soil conditions and promoting melon growth by modulating soil metabolites.